THE NEXT STEP IN ACCOUNTING. - Healy, Robert E. (The Accounting Review, 1938)
Abstract The article focuses on accounting. The author recalls the six years spent largely in asking questions of accountants in the utilities investigation at the Federal Trade Commission. The investigation was largely an accounting investigation. In the light of later experience the author regrets that more attention was not given to the matter of accountants' certificates. Many accountants of the days covered by that investigation acted competently and ethically according to the standards of those days. But there were instances of phony intercompany profits, of write-ups used to create income or to relieve the income accounts of important charges, of profits computed on the sale of securities without even bothering to deduct the cost of the securities, where the accountants certified the statements without exceptions. The author recalls the advent of the Securities Act of 1933, the Securities Exchange Act of 1934, the creation of the Securities and Exchange Commission in 1924, and the Public Utility Holding Company Act in 1935.